PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI KESULITAN BACA TULIS AL QUR’AN DI MADRASAH ALIYAH AL IBROHIMI DESA MANYAREJO KEC. MANYAR KAB. GRESIK - Tinwarul Ahillah; Moh. Murtadho; Devi Wahyu Ertanti (VICRATINA, 2020)
In the Islam ic senior high school Al lbrohimi Manyar Gresik were foun d many student feel di]ficult to read and write Al Quran. The problem is the difliculties experienced by students in reading Holy Qur’an that is need more attention carefully into letters in Qur’an, lack of understanding of tajwid, and lack of fluency in reading Holy Qur’an. ln overcoming student difliculties in the  learning  process,  it  is  better  for  teachers  to have additional media that can be used to measure whether the subject surely delivered. Moreover, it is a lso greatif the teaching process is supported by great facilities to  improve  successfulness   in   the   teaching   and   learning   process. Extrac urricular activities in schools include qiro’ah, scouts, muballighin, and others also help students in improving their ability in reading Al Qur’an.  This research used a qualitative approach. While this type of research is a case study. The results showed that the students were classified as having difficulty in reading and writing Al Quran were reluctant to appear in front of the class, due  to  their  lack  of  enthusiasm  in learning and understanding the reading and writing of the Al Quran. In this case the teacher as a guide, gives responsibility to students wh o have difficulty reading and writing the Al Qura n such as leading  to  pray before the  lesson  begins and the  last The efforts of the teacher ta avercome these difficulties ta provide a ddition al lessans and repeat it for the students who ha ve di]ficulty reading and writing the Al Quran.